2003
DOI: 10.2165/00129784-200303030-00001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selective Serotonin Reuptake Inhibitors on Platelet Activation

Abstract: In recent years a large body of evidence from several longitudinal studies has emerged suggesting that depression is an independent risk factor for cardiovascular disease (CVD) and that the association between depression and increased CVD risk is not merely due to negative mood-driven behavior related with depression. Even though the underlying mechanisms are not well understood, several hypotheses and explanations have been proposed such as increased activation of the hypothalamic-pituitary-adrenal axis, abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 97 publications
0
39
0
1
Order By: Relevance
“…Interestingly, platelets possess different receptors for serotonin (5-HT 2A , 5-HT 3 ) and also the transporter (SERT) in their membranes (Hoyer et al 2002;Stratz et al 2008;Escolar et al 2005;Blakely et al 1991;Hoffman et al 1991;Lesch et al 1993;Ramamoorthy et al 1993). Several studies have shown evidence of a link between increased risk of cardiovascular complications in clinically depressed patients and a possible reduction of this risk after treatment with SSRIs (Schlienger and Meier 2003;Maurer-Spurej et al 2004;Sauer et al 2003). Moreover, our group has recently published an in vitro study in which the effect of serotonin and the SSRI citalopram was evaluated on platelet function (Galan et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, platelets possess different receptors for serotonin (5-HT 2A , 5-HT 3 ) and also the transporter (SERT) in their membranes (Hoyer et al 2002;Stratz et al 2008;Escolar et al 2005;Blakely et al 1991;Hoffman et al 1991;Lesch et al 1993;Ramamoorthy et al 1993). Several studies have shown evidence of a link between increased risk of cardiovascular complications in clinically depressed patients and a possible reduction of this risk after treatment with SSRIs (Schlienger and Meier 2003;Maurer-Spurej et al 2004;Sauer et al 2003). Moreover, our group has recently published an in vitro study in which the effect of serotonin and the SSRI citalopram was evaluated on platelet function (Galan et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…There is clinical evidence supporting the use of behavioral 32 and pharmacological interventions targeting depression to improve cardiovascular prognosis. 33,34 Given the well established relationship between depression and cardiovascular disease, 35 there needs to be a greater awareness of the role of depression as a cardiovascular risk factor in a normotensive population. In addition, longitudinal studies are needed to determine whether interventions aimed at decreasing depression have a positive impact on cardiovascular risk in a normotensive population.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found an increased risk of myocardial infarction among depressed patients (Schlienger and Meier, 2003). Tricyclic antidepressants are not recommended in patients with cardiovascular disease owing to their arrhythmic effects (Cohen et al, 2000, Roose andSpatz, 1998;.…”
Section: Discussionmentioning
confidence: 99%